9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123
2 + 3 + 4 + 5 + 6 = 20
-13 + 6 + 3 = -4
6+4+3=2 when it is a mistake
3 + 4 + 2 + 8 + 6 + 0.3 + 4 + 2 + 8 + 6 + 0.3 + 4 + 2 = 49.6
3+4+6+4=17
3 + 6 + 4 = 13
-6 + (-3) + 4 = -5
6 + 4 + 3 + 4 + 4 + 5 + 4 + 6 + 5 + 4 + 8 + 4 = 57
4 plus 6 plus 3 equals?Add 4 and 6 and get 10, then add 3 and 10 and get 13. Therefore, the answer to 4+6+3 is 13.
-6=-6(-a+2)+3(a-4)
9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123
8 + 8 + 6 + 3 + 4 + 3 = 32
2 + 3 + 4 + 5 + 6 = 20
7 + 5 + 4 + 5 + 3 + 4 + 6 + 5 + 4 + 5 + 6 + 4 + 7 = 65
4 + 6 + 6 + 5 + 5 + 4 + 6 + 5 + 5 + 6 + 5 + 5 + 5 + 3 = 70
2+4+(-3)+(-4) 2+4=6 6+(-3)+(-4)=-1 -3+-4=-7 or 2+4+(-3)+4-4 2+4=6 4-4=0 +(-3)=-3 6-3=3